Clinical features and risk factors of HIV-infected patients with intracerebral hemorrhage: a retrospective study with propensity score matching analysis - Huang, Qiuhui; Chen, Shengri; Huang, Hua; Deng, Xuhui; Cen, Gengyu; Wang, Miao; Liang, Zhijian (Frontiers in Cellular and Infection Microbiology, 2025)
PurposeTo investigate the clinical features and risk factors of the human immunodeficiency virus (HIV)-infected patients with intracerebral hemorrhage (ICH).Patients and methodsThe patients with HIV-infected without ICH group were matched to the group of HIV-infected ICH patients. Logistic regression analysis using 1:1 propensity score matching (PSM) was performed to investigate the independent risk factors for ICH in HIV-infected patients. The receiver operating characteristic (ROC) curve was configured to calculate the optimal predictors of ICH in HIV-infected patients.ResultsA total of 59 HIV-infected patients with ICH and 180 HIV-infected patients without ICH were included. A cohort of 118 patients was ascertained utilizing PSM. Multivariate binary logistic regression analysis revealed that drug abuse-related HIV-infected, prolonged prothrombin time (PT), and elevated triglyceride (TG) levels were independent risk factors of ICH in HIV-infected patients. The ROC curve demonstrated that the combined predictor, composed of drug abuse-related HIV-infected, prolonged PT, and elevated TG levels, exhibited the highest area under the curve (AUC), with a cut-off point at 0.426, sensitivity of 78%, and specificity of 81.4%.ConclusionThe present study revealed that a valuable factor combined with drug abuse-related HIV-infected, prolonged PT, and elevated serum TG levels could serve as predictors of ICH in HIV-infected patients.